Mounting threat of invasive alien fish species in Ganga river system and open water resources of the basin - JOSHI, K D; KUMAR, ADITYA; SRIVASTAVA, S M; SAHU, VIKASH; LAL, KULDEEP K (The Indian Journal of Animal Sciences, 2022)
The authors are grateful to the Director, ICAR-National Bureau of Fish Genetic Resources, Lucknow for the continuous guidance and encouragement to carry out the research work. We also extend sincere thanks to Dr G Rathore, Head, FHM&E Division, ICAR-NBFGR, Lucknow for the facilities and support to carry out this study. The research work is carried out under Institute based project on ‘Risk and benefit assessment modelling for exotic fishes’.